2017
DOI: 10.3390/biomedicines5040070
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Therapeutic Effects of Plant-Extract Synthesized and Traditionally Synthesized Gold Nanoparticles on Alcohol-Induced Inflammatory Activity in SH-SY5Y Cells In Vitro

Abstract: The present study describes potential beneficial and adverse effects of plant-extract synthesized gold nanoparticles (AuNPs) on ethanol toxicity in SH-SY5Y cells. Although kudzu root extract (K), edible-gum extract (G), alone or in combination (KG), reduced Au3+ into AuNPs, the extract’s composition and the reaction temperature determined their size (AuNPKG(90<50<37) << AuNPK (90,50<37) < AuNPG (90<50); the subscript KG, K, or G is extract identification and numerical vales are reaction temperature in Celsius)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 111 publications
(136 reference statements)
0
8
0
Order By: Relevance
“…1552–1587, Shizhen Li), which is the most complete and comprehensive medical book in ancient China, mentions that gold foil (thickness ∼120 nm) has a tranquilizing effect . Gold is one of the components in Tsothel, which is a representative of Tibetan medicine that can protect the liver and cure indigestion. , Drinking gold, consisting of gold nanoparticles (Au NPs), was used to cure many mental illnesses in 16th century Europe and acted as a therapeutic agent for intemperance in America. , Drinking gold could treat arthritis by strengthening bone and relieving the pain of patients. , In the 1890s, researchers found that Au NPs could kill Mycobacterium tuberculosis . In 1939, Au NPs were used as antibacterial agents to cure infections in the clinic .…”
mentioning
confidence: 99%
“…1552–1587, Shizhen Li), which is the most complete and comprehensive medical book in ancient China, mentions that gold foil (thickness ∼120 nm) has a tranquilizing effect . Gold is one of the components in Tsothel, which is a representative of Tibetan medicine that can protect the liver and cure indigestion. , Drinking gold, consisting of gold nanoparticles (Au NPs), was used to cure many mental illnesses in 16th century Europe and acted as a therapeutic agent for intemperance in America. , Drinking gold could treat arthritis by strengthening bone and relieving the pain of patients. , In the 1890s, researchers found that Au NPs could kill Mycobacterium tuberculosis . In 1939, Au NPs were used as antibacterial agents to cure infections in the clinic .…”
mentioning
confidence: 99%
“…Metallic NPs offer more cytotoxicity to cancerous cell lines as compared to normal cells [ 62 , 63 ]. Various mechanisms have been proposed to explain the cytotoxicity mechanism of metallic NPs such as generation of reactive oxygen species (ROS), activation of caspase-3, permeabilization of mitochondrial outer membrane, and specific DNA cleavage, all of which lead to apoptotic, autophagic and necrotic death of the cancer cell [ 64 ]. Figure 6 demonstrates an overview of the proposed cytotoxicity mechanism of metallic NPs against cancerous cells.…”
Section: The Fate Of Cancer Cells Exposed To Npsmentioning
confidence: 99%
“…Larger NPs tend to enter the cells via clathrin-mediated endocytosis. Once they make entry to the cells NPs take different paths within the cell to perform their directed function, either they directly interact with the proteins in cytosol, or they undergo some surface modifications in the lysosome–endosome complex before release into the cytosol [ 64 ]. Inside the cell, NPs trigger a cascade of ROS and start releasing metal ions, which tend to bind with the SH groups of proteins and results in breakage of its S–S bridges.…”
Section: The Fate Of Cancer Cells Exposed To Npsmentioning
confidence: 99%
“…The formation of nanoparticles, nanoemulsions and nanocapsules can improve the functional properties of the garlic extract and increasing their absorption from GIT due to increase surface area and small particles easily penetrate to gut wall and reach to blood stream as well as easily enter to intra cellular and accumulated at target tissue for long period of time (Twegh et al, 2020). (Trujillo et al, 2013) and many researcher that suggest that advantages of NPs are improved bioavailability and multiple drugs loaded in a single nanocarriers, therapeutic efficacy; enhanced shelf-life, improved solubility of poorly water-soluble or drug extract , reduced demand dose that aid to reduce toxicity, and small size aid to elevating uptake of active compound by tissue at target of action so that increase affinity as well as efficacy (Singh, 2017;Worrall et al, 2018 ).…”
Section: Aorta Tissuementioning
confidence: 99%